How Difficult Was It? Metacognitive Judgments About Problems and Their Solutions After the Aha Moment - Moroshkina, Nadezhda V.; Savina, Alina I.; Ammalainen, Artur V.; Gershkovich, Valeria A.; Zverev, Ilia V.; Lvova, Olga V. (Frontiers in Psychology, 2022)
The insight phenomenon is thought to comprise two components: cognitive and affective (the Aha! experience). The exact nature of the Aha! experience remains unclear; however, several explanations have been put forward. Based on the processing fluency theory, the source of the Aha! experience is a sudden increase in processing fluency. In the early stages of problem-solving, processing fluency is relatively low. However, with a change in representation, there is an abrupt increase, accompanied by the emergence of the Aha! experience. We hypothesized that this change would be reflected by whether the individual judges the problem as difficult or easy (i.e., subjective difficulty). Thus, we expected that in a situation whereby the Aha! experience emerges, the problem would be judged as less difficult, regardless of the objective difficulty. We also planned to confirm previously discovered associations between the Aha! experience and accuracy, confidence, and pleasure. To test the proposed hypothesis, during the preliminary stage of the study, we developed a set of 100 remote associate problems in Russian (RAT-RUS) and asked 125 participants to solve problems and indicate the Aha! moment (after solution generation or solution presentation), confidence, difficulty, and likability of each problem. As expected, the Aha! experience often accompanied correct solutions and correlated with confidence judgments. We also found a positive correlation between the Aha! experience and problem likability. As for the main hypothesis, we confirmed that the Aha! experience after the presentation of the solution was associated with a decrease in subjective difficulty. When participants could not solve a problem but experienced the Aha! moment after the solution was presented to them, the problem was perceived as easier than one without the Aha! experience. Thus, our study supports the processing fluency theory and demonstrates the association between the Aha! experience and metacognitive judgments about the accuracy and difficulty of problems.